The expansion of professional education from the Ministry of Agriculture, Industry and Commerce (Brazil, 1909-1930) - Lucas, Marcelly Kathleen Pereira; Medeiros Neta, Olívia Morais de (Cadernos de Educação Tecnologia e Sociedade, 2021)
This work is part of the field of the history of professional education and aims to analyze the expansion of Professional Education in Brazil, from 1909 to 1930, based on the actions of the Ministry of Agriculture, Industry and Commerce. The time frame was selected taking into account the organization of the Ministry. The main sources for the development of this study were the annual reports of the Ministry of Agriculture, Industry and Trade. Based on the mapping and analysis of the sources, we seek to analyze the following questions: How did the Ministry operate the expansion of professional education? How were professional schools distributed throughout Brazil? What kind of schools were created most often? What type of school was most common in each region? To answer these questions, we conducted bibliographic research, categorization and analysis of the sources. The methodology consists of documentary analysis according to Arostegui (2006) and the indicative method according to Ginzburg (1989). The theoretical framework is based on the concept of professional education by Manfredi (2003) and is inserted in the dimension of political history according to Rémond (2003). Through the analysis of the sources we can see that the ministry created and also subsidized agricultural, industrial and commercial schools, with agricultural schools being more common.